2014
DOI: 10.1016/j.neuron.2014.04.007
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep and Movement Differentiates Actions of Two Types of Somatostatin-Expressing GABAergic Interneuron in Rat Hippocampus

Abstract: SummaryNeuropeptides acting on pre- and postsynaptic receptors are coreleased with GABA by interneurons including bistratified and O-LM cells, both expressing somatostatin but innervating segregated dendritic domains of pyramidal cells. Neuropeptide release requires high-frequency action potentials, but the firing patterns of most peptide/GABA-releasing interneurons during behavior are unknown. We show that behavioral and network states differentiate the activities of bistratified and O-LM cells in freely movi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
191
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(211 citation statements)
references
References 73 publications
20
191
0
Order By: Relevance
“…This phase relationship has also been observed in awake rodents (Varga et al, 2012; Katona et al, 2014). How could a similar phase coupling of O-LM and bistratified cells during theta oscillations influence signal integration on CA1 pyramidal neuron dendrites?…”
Section: Behavioral Relevance Of Dendritic Inhibitionsupporting
confidence: 68%
“…This phase relationship has also been observed in awake rodents (Varga et al, 2012; Katona et al, 2014). How could a similar phase coupling of O-LM and bistratified cells during theta oscillations influence signal integration on CA1 pyramidal neuron dendrites?…”
Section: Behavioral Relevance Of Dendritic Inhibitionsupporting
confidence: 68%
“…These studies provided information about the spiking relationship of PV+ and SOM+ cells in relation to theta and ripple oscillations (Royer et al , 2012; Stark et al , 2013; Stark et al , 2014), complementing previous juxtacellular studies, mostly performed under anesthesia (reviewed in Klausberger & Somogyi, 2008; but see Varga et al , 2010; Lapray et al , 2012; Viney et al , 2013; Katona et al , 2014 for waking data). Recent data collected in the medial entorhinal cortex indicated that PV+ cells in this region share many properties with PV+ cells identified in the hippocampus (Royer et al , 2012), such as the shape of their spike waveforms, their high firing rate and the low spatial selectivity of their firing fields (Buetfering et al , 2014).…”
Section: Optogenetics and Physiological Characterization Of Interneuronsmentioning
confidence: 79%
“…Studies using single-cell recordings and labeling in freely behaving animals represent complementary approaches towards an exhaustive knowledge of interneuron physiology in the freely behaving animal because they can provide information about the morphology, expression of multiple markers as well as intracellular properties (Isomura et al , 2009; Lapray et al , 2012; Varga et al , 2012; Viney et al , 2013; Katona et al , 2014). Alternatively, refinement of genetic approaches employed to target distinct functional sub-populations of interneurons (Fenno et al , 2014) will allow a more detailed dissection of the circuit elements involved in specific behaviors.…”
Section: Optogenetics and Physiological Characterization Of Interneuronsmentioning
confidence: 99%
“…Therefore, it will be important determine whether other inhibitory cell types 5861 are also differentially interconnected with distinct CA1PC subpopulations. For instance, interneurons that innervate dendrites 6265 or axon initial segments 6669 may also show preference for CA1PC subgroups to exert subcircuit-selective regulation of input integration and spiking output generation, respectively 6670 .…”
Section: Ca1pc Heterogeneity and Local Microcircuitsmentioning
confidence: 99%